Focused review of sleep wearable technology and its application in sports performance - Kaufman, M. W.; Shetty, M.; Nguyen, C.; Abas, J.; Fredericson, M.; Zeitzer, J. (Current Sports Medicine Reports, 2025)
Sleep is a critical component of quality of life, recovery, and performance both physically and cognitively. Tracking sleep with wearables is increasingly prevalent among individuals; the data that are retrieved from these wearables, however, is of unclear relevance. To update this space, literature was reviewed to examine the implications for good and bad sleepers, the current shortcomings of wearables, their current status usage and literature reports in sports medicine, and the future benefits that these devices may have for athletes and nonathletes alike. Wearables have good performance in detecting sleep but have greater difficulty in discerning between quiet wakefulness and early stages of sleep. The use of summative scores in consumer wearables is opaque, which should make sports medicine providers skeptical of their clinical utility. There is ample opportunity for wearables to be clinically useful and research opportunities to better explore the bidirectional relationship between daytime athletic performance and sleep.